(untitled) (Journal of the College of Basic Education, 2023)
Since the end of World War I, which resulted in the establishment of the Turkish Republic in 1923, the Kurdish issue in Turkey has not found a final solution by successive governments until now. This is due to the lack of trust between the government on the one hand and the Kurdish leaders on the other. In addition to the complications that accompanied it, the most prominent of which was the policy of denial, exclusion, and mutual violence, which was a permanent advocacy for it. Not to mention the Kemalist ideology that arose on the principle of Turkish nationalism and its denial of the culture of national pluralism in Turkey and the lack of recognition of the social and historical realities of the Kurds in southeastern Turkey, who number about Approximately (15) million They were called "Mountain Turks" instead of the Kurds, and they were prevented from using their language and confiscating their culture, which led to them carrying out many revolutions against the Ankara government, which it could not put down by force of arms over the past decades. As soon as the Justice and Development Party came to power in 1922, it sought to find a solution to the Kurdish issue by initiating direct negotiations with Abdullah Ocalan, the leader of the Kurdistan Workers’ Party, to reach a settlement according to the vision of the Justice and Development Party based on achieving security, stability, internal peace, and achieving comprehensive economic advancement in the country. Nevertheless, this step faced many obstacles and obstacles, the most prominent of which is the nationalist trend’s insistence on not recognizing the political and cultural rights of the Kurds, as well as the regional and international external interference, which had a role in not reaching a comprehensive settlement, which led to renewed acts of violence and fighting between the two parties. The research was divided into three main sections, the first topic was titled (the conditions of the Kurds in Turkey under the rule of the Kemalists) and the second topic was titled (the procedures of the government of Tayyip Erdogan and his party to solve the Kurdish issue). The third topic was titled (obstacles and obstacles affecting the solution of the Kurdish issue in Turkey) as well as a conclusion in which the most important conclusions reached by the research were mentioned, and the research relied on many diverse Arab and foreign sources included in the list of sources